2011
DOI: 10.1038/hr.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime risk of stroke and impact of hypertension: estimates from the adult health study in Hiroshima and Nagasaki

Abstract: Very few reports have been published on lifetime risk (LTR) of stroke by blood pressure (BP) group. This study included participants in the Radiation Effects Research Foundation Adult Health Study who have been followed up by biennial health examinations since 1958. We calculated the LTR of stroke for various BP-based groups among 7847 subjects who had not been diagnosed with stroke before the index age of 55 years using cumulative incidence analysis adjusting for competing risks. By 2003, 868 subjects had suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
(32 reference statements)
4
16
0
1
Order By: Relevance
“…These were observed across all the studied index ages as well as on both sexes. Our estimates of LTR of stroke in the Suita study are also consistent with the reported LTR of stroke from the Netherlands [19], United States [20], United Kingdom [21], as well as another study from Japan [22]. The LTRs of stroke for middle-aged men and women were substantial.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These were observed across all the studied index ages as well as on both sexes. Our estimates of LTR of stroke in the Suita study are also consistent with the reported LTR of stroke from the Netherlands [19], United States [20], United Kingdom [21], as well as another study from Japan [22]. The LTRs of stroke for middle-aged men and women were substantial.…”
Section: Discussionsupporting
confidence: 87%
“…Also, it was observed that individuals who maintained or decreased their BP to normal levels had the lowest remaining LTR for stroke, compared with individuals who had or developed hypertension by 55 years of age [27]. Authors from Japan, studying the Radiation Effects Research Foundation Adult Health Study cohort, showed that the LTR of stroke and its subtypes differed across the categories in BP among men and women of index age of 55 years [22]. The LTR of stroke for normotensive men and women was 13.8 and 16.0%, respectively, whereas the LTR of stroke for stage 2 hypertensive men and women were 25.8 and 30.5%, respectively [22].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…[15][16][17] However, these studies did not investigate the effect of blood pressure, by category, on the lifetime risk of these diseases. In this issue of the journal, Takahashi et al 18 present the lifetime risk estimates of stroke according to different levels of blood pressure for middle-aged men and women. The authors analyzed the data relating to the participants enrolled in the Radiation Effects Research Foundation Adult Health Study, who have been longitudinally followed since 1958.…”
mentioning
confidence: 99%